ENHANCING ENERGY EFFICIENCY IN GLASS FACADES THROUGH BIOMIMETIC DESIGN STRATEGIES - Ozturk, Busra; Mutlu-Avinc, Gunes; Arslan-Selcuk, Semra (Univ Bio-Bio, 2024)
The building industry, responsible for a large proportion of energy consumption, is looking for solutions to reduce energy consumption. This study proposes biomimetic facades to ensure thermal comfort. Firstly, it examined biomimetic fa & ccedil;ade systems in the literature. Then, it analyzed the thermoregulation methods of nature, the level of biomimicry, and the strategies used by living things. As a result of the analyses, biological information regarding the three selected phenomena was expanded upon, determining how to transfer the biomimicry method to a building envelope. Energy simulations were conducted on the glass fa & ccedil;ade of the S & uuml;leyman Pasha Bath to evaluate the envelope's energy efficiency. It was found that nature-inspired methods significantly contributed to the building's energy consumption when examining the simulation results of the fa & ccedil;ade designed.
Keywords: biomimicry; facade design; energy efficiency; thermoregulation